Optimasi Produktivitas Karyawan melalui Pelatihan, Disiplin, dan Motivasi Kerja - Fatah, Amir Amrullah (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
Employee productivity is a crucial factor in organizational success. Factors such as training, discipline, and work motivation have been recognized as having a significant impact on individual productivity in the workplace. However, a deeper understanding of how these factors can be optimized to achieve higher productivity remains a relevant research focus. This research aims to investigate the influence of training, discipline and work motivation on employee productivity and to identify optimal strategies for integrating these three factors to improve individual performance. The research was conducted through employee surveys from various industrial backgrounds. Data collection was carried out through a questionnaire that included questions about the level of training received, the level of discipline maintained, perceived work motivation, and the level of productivity generated. Data were analyzed using descriptive statistical methods and regression to evaluate the relationship between these variables. The research results show that proper training, consistent discipline, and high work motivation have a significant positive impact on employee productivity. Strategic integration of these three factors results in better performance and employees who contribute more to organizational goals.